Seeing the faults from the hummocks: tectonic or landslide fault discrimination with LiDAR at Mt Shasta, California - Tortini, Riccardo; van Wyk de Vries, Benjamin; Carn, Simon (Frontiers in Earth Science, 2015)
The detection of active faults around volcanoes is of importance for both seismic and volcanic hazard assessment. The lower flanks of volcanoes are, however, often covered by debris avalanche deposits (DADs) that are highly faulted during transport. Such areas are dissected by faults that delineate deposit hummocks, making it hard to differentiate tectonic from landslide structures. Detailed analysis of DAD surface morphology can detect fault trends not compatible with landslide emplacement, but which do follow regional trends or cut hummocks. Indeed, neotectonic faults may also cut across avalanche structure and morphology and thus be distinguishable. We present evidence from the Mount Shasta DAD of neotectonic deformation along a north-south trending fault. The fault was identified on an airborne LiDAR campaign and then confirmed in the field. The discovery shows the value of high-resolution topographic mapping of such areas, and exposes a previously unknown fault. In this particular case the identified fault is not long, and may not present a strong seismic risk to the sparsely populated area, but the full area of the DAD has not been mapped and there are suggestions from lower resolution datasets that other faults may be present outside the LiDAR coverage, indicating that the Shasta basin could be more seismically active than presently thought. We speculate that this may be part of a westward extension of the Klamath basin rifting. Many DADs at the base of other volcanoes are highly populated and fault detection in these zones could have a significant impact on risk assessment.